Temperature Dependence Evaluation of CO2 Adsorption on Eagle Ford Shale using Isothermal Models: A Comparative Study - Zardari, Zaheer Hussain; Mohshim, Dzeti Farhah (Engineering, Technology & Applied Science Research, 2025)
This study investigates the CO2 adsorption capacity of the Eagle Ford (EF) shale under varying temperatures, utilizing six isothermal adsorption models: Langmuir, Freundlich, Dubinin-Radushkevich (D-R), Sips, Toth, and Brunauer-Emmett-Teller (BET). The shale sample was characterized through Total Organic Carbon (TOC) analysis, X-ray diffraction (XRD), BET surface area analysis, and Field Emission Scanning Electron Microscopy (FESEM) to assess its organic content, mineral composition, pore structure and elemental composition. CO2 adsorption experiments were conducted using a volumetric method at pressures up to 12 MPa and temperatures of 35°C, 55°C, and 70°C. The results revealed that the adsorption capacity increased with pressure but decreased with rising temperature, which is consistent with the exothermic nature of CO2 adsorption. Among the models, Freundlich and Sips provided the best fit for most temperature conditions, highlighting the heterogeneous nature of the shale surface, while the Langmuir, Toth, and D-R models performed well but with slight deviations. The BET model exhibited the poorest fit. Overall, the findings suggest that the EF shale has significant potential for CO2 storage, especially at lower temperatures, with Freundlich and Sips models being the most reliable for predicting adsorption behavior in EF shale formations.